134 Quantitative Assessment of Visual Function for Pituitary Macroadenomas: A Practical Scoring Algorithm. (4th May 2021) - Lee, K S; Jeffrey, S; Bradley, K; Atan, D; Williams, A; Abhinav, K; Teo, M; Nelson, R
Abstract: Introduction: There is a myriad of existing terms by which visual capacity is recorded. The lack of a standardised categorisation of observations commonly results in ambiguities. We report the utility of a visual function score (VFS) in patients managed by transsphenoidal surgery. Method: A VFS (expressed as a percentage) with a maximum score of 20 was calculated for each eye using the Snellen VA (40% weighting: score 0-8) and Humphrey Allergan 30-2 automated visual field (60% weighting: score 0-12). Results: 280 patients (560 eyes) underwent transsphenoidal pituitary adenoma resections with complete pre- and post-operative visual function assessment. Mean age 56 years; 56.4% male. 26.1% were treated by endoscopic technique and 73.9% were treated by microscopic technique. Pre-operative vision was normal in 38.0% eyes. All these had full post-operative vision. In patients with pre-operative visual loss (347 eyes), the mean pre-operative VFS rose from 70.8% to 87.5% post-operatively. 43.8% eyes attained full post-operative vision, 28% improved, and 25.6% remained unchanged. 9 patients (2.6%) had worse immediate post-operative vision. Conclusions: The VFS is a convenient single measure of visual function that may facilitate local and national audit of transsphenoidal surgery. Studies are planned to correlate this with patient reported visual quality of life measures.